Blue mode does not offer any benefit over white light when calculating Lewis score in small-bowel capsule endoscopy - Koulaouzidis, Anastasios (Baishideng Publishing Group Co., Limited, 2012)
AIM: To check the usefulness of blue mode (BM) review in lewis score (LS) calculation, by comparing it with respective LS results obtained by white light (WL) small-bowel capsule endoscopy (SBCE) review and mucosal inflammation as reflected by faecal calprotectin (FC) levels, considered as ‘gold standard’ for this study. METHODS: Computational analysis of our SBCE database to identify patients who underwent SBCE with PillCam(®) and had FC measured within a 30-day period from their test. Only patients with prior colonoscopy were included, to exclude any colon pathology-associated FC rise. Each small bowel tertile was reviewed (viewing speed 8 fps) with WL and BM, in a back-to-back mode, by a single experienced reviewer. LS were calculated after each WL and BM reviews. Pearson rank correlation (rho, r) statistic was applied. RESULTS: Twenty-seven (n = 27, 20F/7M) patients were included. Thirteen (n = 13) had SBCE with PillCam(®)SB1, and the remainder (n = 14) with PillCam(®)SB2. The median level of FC in this cohort was 125 μg/g. LS (calculated in WL SBCE review) correlation with FC levels was r = 0.490 (P = 0.01), while for BM review and LS correlation with FC was r = 0.472 (P = 0.013). CONCLUSION: Although BM is believed to enhance mucosal details i.e., small mucosal breaks, it did not perform better than WL in the calculation of LS in our cohort.